Induction of ICAM 1 expression on bladder tumours by BCG immunotherapy. Issue 4 (April 1994) - Jackson, A M; Alexandroff, A B; McIntyre, M; Esuvaranathan, K; James, K; Chisholm, G D
Abstract : AIMS--To determine the expression of intercellular adhesion molecule 1 and 2 (ICAM 1 and 2) in transitional cell carcinoma cells before and after immunotherapy with Calmette-Guérin bacillus (BCG). METHODS--Frozen sections from 22 untreated bladder carcinomas were immunohistochemically examined with monoclonal antibodies to ICAM 1 and 2. Urinary cytospin slides were made for six patients for each of the six clinical instillations which constitute a therapeutic course. These slides were also stained for ICAM 1 and for leucocyte function associated antigen 1 (LFA 1). RESULTS--Bladder cancer cells did not essentially express either ICAM 1 or 2, but cells in the stromal areas surrounding tumour expressed both these antigens. After repeated instillations of BCG organisms ICAM 1 positive normal and neoplastic epithelial cells were observed in the urine. Cells obtained from the first three instillations expressed lower densities of ICAM 1 than those from the later instillations. Many neutrophils expressing LFA-1 and some lymphocytes were also noted in the cytospin slides and some of these were conjugated to tumour cells expressing ICAM 1. Six months after treatment a single maintenance dose of BCG induced ICAM 1 expression. CONCLUSION--Untreated superficial bladder carcinoma cells do not express ICAM 1 or 2, but these important immunological molecules were expressed in the stromal areas of tissue. Importantly, neoplastic cells in the urine expressed ICAM 1 after immunotherapy. This molecule can render bladder tumour cells vulnerable to non-antigen specific cytotoxicity mediated by activated lymphocytes.